Chalcididae (Hymenoptera) parasitoides de desfolhadores (Lepidoptera) de eucalipto (Myrtaceae) no Novo Mundo - Simoneli, Bruna Cortat (2023)
The family Chalcididae (Hymenoptera, Chalcidoidea) is widely distributed around the globe and assembles about 1584 described species. The family is diversified in the New World, especially in the Neotropical region, which presents about 472 species in 29 genus. Most chalcidid wasps is primary parasitoids of larvae and pupae of holometabolous insects (including lepidopterans, dipterans and coleopterous) and, some of their hosts are of importance as agricultural pests, such as some eucalyptus defoliator. Here is presented a synopsis of the species of Chalcididae parasitoid of lepidopteran defoliator pests of eucalyptus in the New World. This synopsys includes a checklist of the parasitoid species and their defoliator hosts, associated plant, geographic distribution, previously and new records to each host-parasitoid association, and comments and corrections to the records. Identification tools such as diagnoses, identification key and illustrations also are presented. This synopsys include 18 Chalcididae species, six belonging to Brachymeria and 12 to Conura (two undescribed), 19 host species and 46 host-parasitoid associations (17 as new records).